The University of California San Francisco (UCSF) Training Program in Implementation Science: Program Experiences and Outcomes - Shete, Priya B.; Gonzales, Ralph; Ackerman, Sara; Cattamanchi, Adithya; Handley, Margaret A. (Frontiers in Public Health, 2020)
Purpose: We evaluated outcomes of trainees who have completed the Certificate program in Implementation Science at the University of California San Francisco. Methods: All students who completed the in-person Certificate Program between 2008 and 2015 (n = 71), or the online Certificate Program between 2016 and 2017 (n = 13), were eligible for our study. We assessed the potential impact of the Certificate Program on the professional development of trainees, through participant surveys on their self-reported level of comfort with pre-defined competencies, and on academic productivity. Results: Of eligible trainees, 54 in-person (77%) and 13 online (100%) Certificate Program participants completed surveys. In-person trainees reported a total of 147 implementation science-related publications in peer-reviewed journals (median 3 publications/trainee, IQR 1–15). Thirty-four trainees (63%) reported being a Principal Investigator (PI) of 64 funded implementation science-related grants (median 2 grants/trainee, IQR 1–4). Fifteen percent (15%, n = 8) of participants reported receiving an NIH grant on which they were the PI, including R01 or P01 level funding (n = 4, 7%) and K awards (n = 3, 6%). Both in-person and online trainees reported median high to moderate confidence for all 12 competencies assessed. Confidence waned in skills aligning with later stages of implementation research for all trainees. Conclusion: The moderate to high confidence in all competencies assessed and reported high level of academic productivity support the benefits of intensive, graduate-level training focused on applied methods to support career development of implementation scientists.